Pengendalian Kebersihan Seat Assembly Filter dengan Metode 7 Tools - Yazid Bustommy, Abby; Meliana, Fitri; Koswara, Ade (Universitas Tangerang Raya, 2021)
The automotive and heavy duty parts industry (heavy equipment) has world-class quality guaranteed. To be able to compete in the era of globalization, it is necessary to improve quality, service and prices that can compete with other automotive parts companies which allow us as one of the companies that have been certified to be able to meet the requirements demanded by customers. The company itself already has the two criteria above that can represent this company as one of the competitors to be reckoned with in the automotive industry and heavy duty (heavy equipment), it's just that one of the criteria above is that the quality of the product is not close to what is expected for consumers. . Based on the production data obtained from the Company, it is known that the total production in July - September was 2,126,197 pcs, with a total number of gross seat assy defects of 42,046 pcs, with 19,775.2 ppm. Of course, this will result in considerable losses for the company if it is not repaired. Coupled with the number of customer claims that were repeated 9 times and the company had to pay the cost of poor quality caused by the claim of Rp 18,980,013.67.